Steroid tape: A promising adjunct to scar management - Ioannis Goutos; Rei Ogawa (SAGE Publishing, 2017)
Introduction: Intralesional steroid administration is a popular adjunct to scar management with numerous reports in the literature appraising this modality in hypertrophic and keloid scars. The percutaneous delivery of steroids using adhesive tape is an alternative modality, which was first described in the dermatological literature in the 1960s. It is infrequently used in most countries apart from the Orient, where it represents one of the mainstays of specialist scar management protocols. Methods: An English and Japanese literature review was performed and reports were stratified using the Joanna Briggs Institute Levels of Evidence. Data were extracted relating to the maximum dose of steroid that can be delivered safely, the reported therapeutic efficacy, as well as the side effects associated with the percutaneous delivery of steroids. Discussion: Steroid tape has the potential to be a safe and patient-friendly adjunct to scar management for carefully selected cases of keloid and hypertrophic scars. The main limitation for its widespread adoption is the lack of data to enable the determination of safe exposure thresholds in adult and paediatric patients. Conclusion: Despite the existing encouraging reports regarding the potential to be a useful adjunct in scar management, steroid tape is not widely used apart from a limited number of scar services worldwide. Further research is warranted to delineate the role of this modality in specialist scar management protocols.